(untitled) (Fountain Journal of Natural and Applied Sciences, 2024)
This research investigated the impact of incorporating green synthesised copper oxide nanoparticles into nanoporous carbon counter electrodes to enhance photovoltaic performance in Monolithic Dye-Sensitized Solar Cells (MDSSCs). Copper oxide nanoparticles were successfully synthesised using an extract from Ocimum gratissimum leaves. Optical absorption between 250 nm and 400 nm confirmed the formation of copper oxide nanoparticles. XRD patterns indicated the crystalline nature of the copper oxide nanoparticles, with an average crystallite size of 47.9 nm. FTIR analyses identified chemical bonds potentially responsible for nanoparticle formation. MDSSC performance evaluation demonstrated a significant 3.5% increase in efficiency over the cells without nanoparticles; this translates to a 105.9% increase in efficiency observed for cells with the nanoparticles. The incorporation of green-synthesized copper oxide nanoparticles into the counter electrode of MDSSCs exhibited an eco-benign and even dispersion, suggesting its potential as a promising nanomaterial for DSSC applications. Keywords: Green Synthesis; Nanoparticles; Copper Oxide; Counter Electrode; Monolithic Dye -Sensitised Solar Cell